2018
DOI: 10.1021/acsanm.8b01585
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Cross-Linked Chitin Nanocrystal Scaffolds for Drug Delivery

Abstract: Chitin nanocrystals (ChNCs), prepared by acid hydrolysis of chitin, exhibit a uniform needlelike morphology and high dispersion stability in aqueous solutions, which makes them good candidates for drug delivery. Porous ChNC scaffolds were freeze-dried from different concentrations of ChNC dispersions and then cross-linked by a reaction with glutaraldehyde. Various techniques, including scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Some findings suggested that primary cells or stem cells responded differently to nanoparticle exposure as compared to the other cell lines. , The unique properties ensure stem cells to possess the potential applications include stem cell therapy, tissue engineering, drug delivery, and so on. Therefore, evaluating the hazardous effects of 1D nanoparticles on stem cells is significant. , In our previous studies, it was proved that ChNCs and HNTs could be used as the carrier of antitumor drugs. , Based on these applications, UMR-106 was chosen as the tumor cell model for the cytotoxicity test. As shown in Figure , both mBMSCs and UMR-106 were alive and dead cells (orange color) were rare at the concentration of ChNCs in the range of 2.5–200 μg/mL from the LIVE/DEAD staining images.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some findings suggested that primary cells or stem cells responded differently to nanoparticle exposure as compared to the other cell lines. , The unique properties ensure stem cells to possess the potential applications include stem cell therapy, tissue engineering, drug delivery, and so on. Therefore, evaluating the hazardous effects of 1D nanoparticles on stem cells is significant. , In our previous studies, it was proved that ChNCs and HNTs could be used as the carrier of antitumor drugs. , Based on these applications, UMR-106 was chosen as the tumor cell model for the cytotoxicity test. As shown in Figure , both mBMSCs and UMR-106 were alive and dead cells (orange color) were rare at the concentration of ChNCs in the range of 2.5–200 μg/mL from the LIVE/DEAD staining images.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ChNCs were explored as carriers of methylparaben to prepare durable antimicrobial cotton textiles . Our laboratories have also investigated the use of ChNC scaffolds in controlling the release of curcumin for anticancer therapy . However, studies on the toxicity of ChNCs especially using an in vivo model are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds based on CMC and CS have been prepared via polyelectrolyte charge complexation (PEC) followed by freeze-drying and reported for tissue engineering applications. , Even though they can easily be fabricated via PEC, most products lack dimensional stability or load-bearing capacity in biological environments under physiological conditions (37 °C, pH 7.4). Thus, the properties of scaffolds have been improved by chemical cross-linking, but this procedure often requires chemical modification or prior chemical treatment with reactive functional groups. This can be associated with cytotoxicity and require extensive purification. Therefore, an alternative process, namely, dehydrothermal (DHT) treatment in the dry state after PEC can be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The glycol chitin can easily generate thermosensitive hydrogels in PBS solution (Zhengzheng Li, Cho, Kwon, Janát‐Amsbury, & Huh, ). Like cellulose, chitin nanofibrils and nanowhiskers have attracted great attention as drug delivery scaffolds (Morganti et al, ; Ou, Zheng, Zhao, & Liu, ). The most used chitin derivative is chitosan.…”
Section: Polysaccharidesmentioning
confidence: 99%